Preparation method and device of hexagonal boron nitride nanosheet, heat dissipation coating and aluminum alloy heat sink
Patent Information
- Application Number
- CN202410544459.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-30
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2044-04-30
AI Technical Summary
Existing technologies for preparing hexagonal boron nitride nanosheets suffer from problems such as violent reactions that generate highly corrosive gases and introduce numerous defects, resulting in poor nanosheet quality and limiting their application in the field of heat dissipation materials.
A magnesium thermal combustion synthesis reaction was carried out using a mixture of magnesium powder, magnesium oxide powder, and boron oxide powder. Combined with vacuum treatment and acid washing processes, hexagonal boron nitride nanosheets with few defects and high aspect ratio were prepared, and the reaction conditions were controlled by a specific device.
High-quality hexagonal boron nitride nanosheets were successfully prepared, significantly improving their chemical stability and thermal conductivity, thereby enhancing the heat dissipation performance of heat dissipation coatings and aluminum alloy heat sinks.
Smart Images

Figure CN118419865B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of nanomaterial preparation, and more particularly to a method, apparatus, heat dissipation coating, and aluminum alloy heat sink for preparing hexagonal boron nitride nanosheets. Background Technology
[0002] Hexagonal boron nitride (h-BN) nanosheets are composed of multiple layers of hexagonal boron nitride stacked together. Hexagonal boron nitride nanosheets have mechanical and thermal conductivity properties comparable to graphene, and have superior chemical and thermal stability, making them a relatively ideal heat dissipation material.
[0003] Existing technologies use a mixture of boric acid, ammonium salt, and magnesium powder to prepare disc-shaped hexagonal boron nitride polycrystalline powder. Ammonium salt is used as a diluent to decompose and form gas channels, improving reaction efficiency. However, this reaction generates large amounts of highly corrosive gases, posing a potential threat to equipment and personnel. Furthermore, the vigorous reaction introduces numerous defects onto the surface of the prepared hexagonal boron nitride powder, affecting its quality. In recent years, researchers have continuously explored green, energy-saving, and environmentally friendly synthesis methods to prepare high-quality hexagonal boron nitride nanosheets, including mechanical separation, chemical vapor deposition, and solid-phase chemical reaction methods. However, these methods have limitations; the resulting hexagonal boron nitride nanosheets exhibit inconsistent quality, low aspect ratios, and severe defects, hindering the further development of hexagonal boron nitride in related application fields. Summary of the Invention
[0004] This invention provides a method for preparing hexagonal boron nitride nanosheets. This method is simple and easy to implement, and can prepare hexagonal boron nitride nanosheets with few defects and high aspect ratio by limiting the size of raw materials and diluents.
[0005] The present invention also provides an apparatus for preparing hexagonal boron nitride nanosheets, which is applied to the above-mentioned method for preparing hexagonal boron nitride nanosheets.
[0006] The present invention also provides a hexagonal boron nitride nanosheet prepared by the above preparation method.
[0007] The present invention also provides an apparatus for preparing hexagonal boron nitride nanosheets using the above-described preparation method.
[0008] The present invention also provides a heat dissipation coating. Since the coating includes the above-mentioned hexagonal boron nitride nanosheets, it can effectively improve the heat exchange efficiency of high-power devices.
[0009] The present invention also provides an aluminum alloy heat sink, which has excellent heat dissipation capacity because it includes the above-mentioned heat dissipation coating.
[0010] In a first aspect, the present invention provides a method for preparing hexagonal boron nitride nanosheets, comprising the following steps:
[0011] A mixture containing magnesium powder, magnesium oxide powder and boron oxide powder is pressed into sheets, vacuumed, and then nitrogen is introduced to carry out a magnesium thermal combustion synthesis reaction. The solid product obtained from the reaction is cooled to room temperature and then acid-washed to obtain the hexagonal boron nitride nanosheets.
[0012] The magnesium oxide powder has a D50 of 200-300 nm and a D90 of 400-500 nm.
[0013] In an optional embodiment, the pressure of nitrogen gas introduced is 0.1-1 MPa.
[0014] In an optional embodiment, the magnesium oxide powder accounts for a molar proportion greater than 0.3 of the mixture, and the molar ratio of boron oxide powder to magnesium powder is 1-2:2-4.
[0015] Secondly, the present invention provides a hexagonal boron nitride nanosheet prepared by the above-described preparation method.
[0016] Thirdly, the present invention provides an apparatus for preparing hexagonal boron nitride nanosheets, applied to the preparation method of hexagonal boron nitride nanosheets as described above, comprising a reaction vessel, a tungsten wire, a vacuum pump, an inlet valve, an outlet valve, two thermocouples, and a graphite crucible. The graphite crucible and the tungsten wire are respectively disposed inside the reaction vessel, and the tungsten wire is also connected to the graphite crucible. Both thermocouples are disposed on the reaction vessel and are connected to the graphite crucible. The vacuum pump, the inlet valve, and the outlet valve are respectively connected to the interior of the reaction vessel.
[0017] Fourthly, the present invention provides a heat dissipation coating comprising the aforementioned hexagonal boron nitride nanosheets.
[0018] Fifthly, the present invention provides an aluminum alloy heat sink, comprising an aluminum alloy substrate and a heat dissipation coating disposed on the aluminum alloy substrate, wherein the heat dissipation coating comprises the aforementioned hexagonal boron nitride nanosheets, or is made from the aforementioned heat dissipation coating material.
[0019] In an optional embodiment, it is prepared by a method comprising the following processes:
[0020] 1) The hexagonal boron nitride nanosheets, silane coupling agent, organosilicon resin and solvent are mixed to obtain a heat dissipation coating;
[0021] 2) Apply the heat dissipation coating to the surface of the aluminum alloy substrate and perform a curing process.
[0022] In an optional embodiment, it is prepared by a method comprising the following processes:
[0023] 1) The hexagonal boron nitride nanosheets were dispersed in an alkaline solution and then heated to obtain hydroxylated hexagonal boron nitride nanosheets;
[0024] 2) Hydroxylated hexagonal boron nitride nanosheets, silane coupling agent, and solvent are mixed to obtain a heat dissipation coating;
[0025] 3) Immerse at least one surface of an aluminum alloy substrate in an acid solution for a period of time to obtain an aluminum alloy substrate including at least one rough surface, wherein the roughness of the rough surface is 1.5-1.8 μm;
[0026] 4) Spray a silane coupling agent onto the rough surface of the aluminum alloy substrate to form a silane coupling agent bonding layer, and then spray the heat dissipation coating and perform a curing treatment.
[0027] In an optional embodiment, the aluminum alloy heat sink satisfies the following formulas 1-2:
[0028] 0.1≤(MN) / N≤0.15 Equation 1,
[0029] 30μm≤Q≤50μm Equation 2,
[0030] Wherein, M is the heat exchange efficiency of the aluminum alloy radiator under conditions of 80-100℃, N is the heat exchange efficiency of the aluminum alloy substrate under conditions of 80-100℃, and Q is the thickness of the heat dissipation coating.
[0031] The preparation method provided by this invention can produce hexagonal boron nitride nanosheets with few defects and high aspect ratio. Specifically, the aspect ratio of the hexagonal boron nitride nanosheets is 250 to 800. Moreover, the preparation method has strong controllability and good batch stability.
[0032] Furthermore, the aluminum alloy radiator provided by the present invention, due to the presence of a heat dissipation coating including the aforementioned hexagonal boron nitride nanosheets, can improve its heat exchange efficiency by 10-15% under conditions of 80-100°C compared to when no heat dissipation coating is provided. Attached Figure Description
[0033] The accompanying drawings, which are incorporated in and form part of this specification, illustrate embodiments consistent with the invention and, together with the description, serve to explain the principles of the invention.
[0034] Figure 1 An apparatus for preparing hexagonal boron nitride nanosheets according to a specific embodiment of the present invention;
[0035] In the diagram, 100-mixed materials, 101-reaction vessel, 102-tungsten wire, 103-vacuum pump, 104-inlet valve, 105-outlet valve, 106-thermocouple, 107-graphite crucible;
[0036] Figure 2 The XRD characterization spectra of the powder samples obtained in step 8 of Examples 1-5;
[0037] Figure 3 The images shown are SEM images of the powder samples obtained in step 8 of Examples 1, 3, and 4, where (a) and (b) are SEM images of the powder samples obtained in step 8 of Example 1 at different magnification ratios, (c) and (d) are SEM images of the powder samples obtained in step 8 of Example 3 at different magnification ratios, and (e) and (f) are SEM images of the powder samples obtained in step 8 of Example 4 at different magnification ratios.
[0038] Figure 4 The XRD characterization spectra of the hexagonal boron nitride nanosheets in Example 1 before and after acid washing treatment are shown.
[0039] Figure 5 The images shown are SEM images of the hexagonal boron nitride nanosheets of Example 4, where (a) and (b) are SEM images of the hexagonal boron nitride nanosheets of Example 4 at different magnification ratios, respectively.
[0040] Figure 6 The images shown are high-resolution images and electron diffraction patterns of hexagonal boron nitride nanosheets from Example 4. In the images shown, (a) is a high-resolution image of the hexagonal boron nitride nanosheets, (b) is a magnified view of the red box portion in (a), and (c) is an electron diffraction pattern of the hexagonal boron nitride nanosheets.
[0041] Figure 7 AFM image of the hexagonal boron nitride nanosheets of Example 4;
[0042] Figure 8 XRD patterns of hexagonal boron nitride nanosheets synthesized in different batches;
[0043] Figure 9 A schematic diagram of the apparatus used to test the heat exchange efficiency of a test case. Detailed Implementation
[0044] To enable those skilled in the art to better understand the present invention, the present invention will be further described in detail below. The specific embodiments listed below are merely descriptions of the principles and features of the present invention, and the examples are only for explaining the present invention and are not intended to limit the scope of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0045] In this application, the term "magnesium thermal combustion synthesis reaction" is also known as magnesium thermal reduction self-propagating high-temperature synthesis. The reaction begins with a rapid increase in temperature within a short period of time. This rapid temperature increase indicates that the combustion synthesis chemical reaction proceeds quickly. The temperature can rise rapidly to a maximum of thousands of degrees Celsius, and then the process of the temperature slowly decreasing is the process of the combustion synthesis reaction ending.
[0046] In a first aspect, the present invention provides a method for preparing hexagonal boron nitride nanosheets, comprising the following steps:
[0047] A mixture containing magnesium powder, magnesium oxide powder and boron oxide powder is pressed into sheets, placed in a reaction vessel, vacuumed, and then nitrogen is introduced to carry out a magnesium thermal combustion synthesis reaction. The solid product obtained from the reaction is cooled to room temperature and then acid-washed to obtain the hexagonal boron nitride nanosheets.
[0048] The magnesium oxide powder has a D50 of 200-300 nm and a D90 of 400-500 nm.
[0049] The above preparation method uses magnesium oxide powder as a diluent. On the one hand, it provides nitridation sites for the nucleation and growth of hexagonal boron nitride nanosheets, effectively inhibiting the growth of hexagonal boron nitride crystals. Moreover, by controlling the particle size distribution of magnesium oxide, it can reduce the introduction of a large number of structural defects during the growth of hexagonal boron nitride nanosheets due to excessively high local temperatures during the reaction process, thus obtaining hexagonal boron nitride nanosheets with relatively complete crystal structures and large aspect ratios. On the other hand, compared with the widely used ammonium salts such as ammonium chloride as diluents in the prior art, the preparation method of this invention can also avoid the generation of a large amount of highly corrosive gases during the reaction process, which poses a potential threat to equipment and personnel.
[0050] It is understandable that the completion of the above-mentioned magnesium thermal combustion synthesis reaction can be determined by real-time temperature measurement using thermocouples.
[0051] Since hexagonal boron nitride nanosheets have excellent chemical stability and good acid resistance, the present invention performs acid washing on the solid product, which can remove impurities such as magnesium oxide without affecting the structure of the hexagonal boron nitride nanosheets. For example, the solid product obtained by the reaction of the present invention is washed in a 1 mol / L hydrochloric acid solution for 2 to 3 hours. After acid washing, the product is further subjected to deionized water washing, vacuum filtration and freeze drying.
[0052] Here, D50 and D90 represent the particle size values corresponding to 50% and 90% (by volume) of the cumulative particle size distribution curve, respectively, which are generally obtained by testing with a laser diffraction particle size distribution instrument.
[0053] The present invention does not specifically limit the particle size of magnesium powder and boron oxide powder. For example, magnesium powder with a particle size of 3-5 μm and magnesium oxide powder with a particle size of 5-10 μm can be selected.
[0054] In one specific embodiment, the pressure of the nitrogen gas introduced is 0.1-1 MPa. The pressure of the nitrogen gas introduced affects the rate and extent of the reaction. If the pressure is less than 0.1 MPa, the reactants will not react sufficiently, and the products may contain unreacted magnesium powder in addition to hexagonal boron nitride nanosheets and magnesium oxide. If the pressure is greater than 1 MPa, the system pressure may become too high during the reaction, posing a safety hazard.
[0055] In one specific embodiment, the magnesium oxide powder accounts for a molar proportion greater than 0.3 of the mixture, and the molar ratio of boron oxide powder to magnesium powder is 1-2:2-4. The magnesium oxide content, combined with the nitrogen pressure within the scope of this invention, can be further increased to avoid the formation of Mg3B2O6 byproducts. Furthermore, by adjusting the molar ratio of magnesium powder, magnesium oxide powder, and boron oxide powder, the morphology of the hexagonal boron nitride nanosheets can be further adjusted within a certain range.
[0056] For example, the molar ratio of magnesium oxide powder to the mixture includes, but is not limited to, any one of the following values: 0.35, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1, etc.
[0057] In one specific embodiment, the magnesiac combustion synthesis reaction is initiated by an electric contact with a tungsten filament. Monitoring the temperature-time curve during the reaction reveals a rapid temperature increase within a short period. This rapid temperature rise indicates a fast-progressing combustion synthesis chemical reaction. The highest point on the curve represents the maximum temperature achievable by the combustion synthesis reaction, reaching up to 1600℃. The subsequent slow temperature decrease represents the end of the combustion synthesis reaction and the natural cooling of the sample. By placing thermocouples at two points spaced a certain distance (L), the time difference (Δt) between the combustion wave (the point of highest temperature) at these two points is measured. The combustion wave velocity (Vc) can be calculated as the ratio of L to time (Δt). In this experiment, the measured combustion wave propagation velocity was 2.56 mm / s, indicating that it conforms to typical gas-solid combustion synthesis reaction characteristics.
[0058] Secondly, the present invention provides an apparatus for preparing hexagonal boron nitride nanosheets, combined with Figure 1 The device is described in detail as including a reaction vessel 101, a tungsten wire 102, a vacuum pump 103, an inlet valve 104, an outlet valve 105, two thermocouples 106, and a graphite crucible 107. The graphite crucible and the tungsten wire are respectively disposed inside the reaction vessel, and the tungsten wire is also connected to the graphite crucible. The two thermocouples are both disposed on the reaction vessel and are both connected to the graphite crucible. The vacuum pump, the inlet valve, and the outlet valve are respectively connected to the interior of the reaction vessel.
[0059] It is understood that when the device is in use, the mixture 100 is placed inside the reactor 101.
[0060] Thirdly, the present invention provides a hexagonal boron nitride nanosheet prepared by the above preparation method.
[0061] In one specific embodiment, the hexagonal boron nitride nanosheets are composed of single-crystal hexagonal boron nitride nanosheets, wherein the aspect ratio (length to thickness ratio) of the single-crystal hexagonal boron nitride nanosheets is 250–800. The structure of the hexagonal boron nitride nanosheets affects their thermal conductivity; hexagonal boron nitride nanosheets within the aforementioned size range can effectively construct a thermally conductive network on the coating substrate, thereby improving the thermal conductivity of the coating.
[0062] Fourthly, the present invention provides a heat dissipation coating comprising the aforementioned hexagonal boron nitride nanosheets.
[0063] Fifthly, the present invention provides an aluminum alloy heat sink, comprising an aluminum alloy substrate and a heat dissipation coating disposed on the aluminum alloy substrate, wherein the heat dissipation coating comprises the aforementioned hexagonal boron nitride nanosheets, or is made from the aforementioned heat dissipation coating material.
[0064] The aluminum alloy matrix mentioned above includes a matrix containing metallic aluminum. As for the proportion of metallic aluminum and the types of other metals, the present invention does not impose any particular limitation.
[0065] In one specific embodiment, it is prepared by a method including the following processes:
[0066] 1) The hexagonal boron nitride nanosheets, silane coupling agent, organosilicon resin and solvent are mixed to obtain a heat dissipation coating;
[0067] 2) Apply the heat dissipation coating to the surface of the aluminum alloy substrate and perform a curing process.
[0068] For example, the silane coupling agents mentioned above include, but are not limited to, at least one of silane coupling agent KH550, silane coupling agent 570, and silane coupling agent 560, preferably silane coupling agent KH550.
[0069] The aforementioned organosilicon resins include, but are not limited to, at least one of methyl silicone resin, phenyl silicone resin, fluorosilicone resin, polyester silicone resin, and phenolic silicone resin, preferably methyl silicone resin with a viscosity (25°C) of 800 mPa·s–1600 mPa·s.
[0070] For example, by weight, the above-mentioned heat dissipation coating includes 70-85 parts of the hexagonal boron nitride nanosheets, 0.5-1.5 parts of silane coupling agent, and 15-30 parts of organosilicon resin.
[0071] In one specific embodiment, it is prepared by a method including the following processes:
[0072] 1) The hexagonal boron nitride nanosheets were dispersed in an alkaline solution and then heated to obtain hydroxylated hexagonal boron nitride nanosheets;
[0073] 2) Hydroxylated hexagonal boron nitride nanosheets, silane coupling agent, and solvent are mixed to obtain a heat dissipation coating;
[0074] 3) Immerse at least one surface of an aluminum alloy substrate in an acid solution for a period of time to obtain an aluminum alloy substrate including at least one rough surface, wherein the roughness of the rough surface is 1.5-1.8 μm;
[0075] 4) Spray a silane coupling agent onto the rough surface of the aluminum alloy substrate to form a silane coupling agent bonding layer, and then spray the heat dissipation coating and perform a curing treatment.
[0076] Typically, heat dissipation coatings incorporate a large amount of organic resin to maintain adhesion to the radiator surface. However, organic resins are prone to cracking and brittleness after prolonged use, causing parts of the heat dissipation coating to fall off and affecting the radiator's heat dissipation stability. Furthermore, adding a large amount of organic resin to the heat dissipation coating can negatively impact the heat dissipation performance of active components such as hexagonal boron nitride nanosheets. In this embodiment, by employing a silane coupling agent bonding layer to tightly connect the rough surface of the aluminum alloy substrate to the heat dissipation coating, the need for additional organic resin binders in the heat dissipation coating can be avoided. This extends the service life of the heat dissipation coating while further improving the heat dissipation performance of the heat sink metal sheets.
[0077] For example, the thickness of the silane coupling agent connecting layer is less than 20 μm; more preferably, the silane coupling agent is sprayed onto the rough surface of the aluminum alloy substrate until the rough surface is wetted.
[0078] For example, the heat dissipation coating includes 70-85 parts of hexagonal boron nitride nanosheets and 0.5-1.5 parts of silane coupling agent.
[0079] For example, the silane coupling agents mentioned above include, but are not limited to, at least one of silane coupling agent KH550, silane coupling agent 570, and silane coupling agent 560, preferably silane coupling agent KH550.
[0080] It is understood that the purpose of the above heat treatment is to hydroxylate the hexagonal boron nitride nanosheets. The heating conditions can be adjusted as needed by those skilled in the art, for example, heating at 100-200°C for 1-2 hours. Exemplarily, the alkaline solution can be a sodium hydroxide solution or a potassium hydroxide solution, and its concentration is not particularly limited in this invention; for example, an aqueous sodium hydroxide solution with a mass percentage of 8-12% can be used.
[0081] In one specific embodiment, the aluminum alloy heat sink satisfies the following formulas 1-2:
[0082] 0.1≤(MN) / N≤0.15 Equation 1,
[0083] 30μm≤Q≤50μm Equation 2,
[0084] Wherein, M is the heat exchange efficiency of the aluminum alloy radiator under conditions of 80-100℃, N is the heat exchange efficiency of the aluminum alloy substrate under conditions of 80-100℃, and Q is the thickness of the heat dissipation coating.
[0085] For example, the thickness of the heat dissipation coating is any value among 35μm, 40μm, 45μm, 47μm, and 50μm.
[0086] The present invention will be further described below with reference to specific embodiments:
[0087] Example 1
[0088] This example provides a hexagonal boron nitride (h-BN) nanosheet, the preparation method of which uses... Figure 1 The device shown includes the following steps:
[0089] S1: Prepare the required raw materials, including magnesium powder (Mg), magnesium oxide powder (MgO) and boron oxide powder (B2O3); wherein, the particle size of Mg is 3μm, the particle size of B2O3 is 10μm, and the D50 of MgO is 300nm and the D90 is 500nm.
[0090] S2: Mix Mg powder, B2O3 and MgO in different molar ratios (see Table 1 for details) to obtain a mixture of 100g.
[0091] S3: Place the mixture into a rectangular graphite crucible 107 with porous carbon felt, and place thermocouples at two fixed intervals.
[0092] S4: Place the rectangular container inside the high-pressure reactor 101;
[0093] S5: Vacuum is drawn into the high-pressure reactor 101 by connecting vacuum pump 103;
[0094] S6: Nitrogen gas is introduced through the gas inlet valve 104 connected to the high-pressure reactor 101. The pressure is shown in Table 1. The reaction is triggered by energizing the tungsten wire 102. The temperature after the reaction is monitored by thermocouple measurement until it reaches room temperature, and a solid product is obtained.
[0095] S7: Allow the solid product to cool naturally for at least 2 hours;
[0096] S8: Grind the cooled solid product to obtain powder;
[0097] S9: Place the powder in a 1 mol / L hydrochloric acid solution for cleaning for 2-3 hours;
[0098] S10: The acid-washed powder was sequentially washed with deionized water, vacuum filtered, and freeze-dried to obtain 8g of hexagonal boron nitride nanosheets.
[0099] Example 2-10
[0100] Each provides a hexagonal boron nitride nanosheet, and its preparation method uses... Figure 1 The device shown follows the same steps as in Example 1, except that the parameters shown in Table 1 are changed.
[0101] Table 1:
[0102]
[0103] Comparative Example 1
[0104] The results are basically the same as in Example 4, except that the D50 of MgO is 600 nm and the D90 is 800 nm, as shown in Table 1.
[0105] Comparative Example 2
[0106] The method is basically the same as in Example 4, except that MgO powder is replaced with ammonium chloride (NH4Cl).
[0107] Test Example 1
[0108] (1) XRD characterization spectra were obtained for the powder samples obtained in step 8 of Examples 1-10 and Comparative Examples 1-2. The XRD results for the powder samples in Examples 1-5 are shown below. Figure 2 (The powder samples of Examples 1-5 are marked as 1 to 5 in the figure).
[0109] The XRD patterns of all the above samples contained diffraction peaks of hexagonal boron nitride nanosheets, indicating that hexagonal boron nitride nanosheets were successfully prepared. Figure 2It can be seen that, in addition to the diffraction peaks of hexagonal boron nitride nanosheets and MgO, the powder samples in Examples 1-3 and 5 also contain diffraction peaks of Mg3B2O6. This is mainly due to the reaction of residual B2O3 and MgO in the reaction product at high temperature. By controlling the content of MgO diluent and the nitrogen pressure during the combustion synthesis process, the formation of Mg3B2O6 byproduct can be reduced or avoided. For example, in the raw material formulation of Example 4, when the amount of diluent MgO is 4.5 mol and the N2 pressure is 0.5 MPa, the formation of Mg3B2O6 byproduct can be almost avoided. In addition, the XRD characterization spectra of the powder samples in Examples 6-10 also contain diffraction peaks of hexagonal boron nitride nanosheets, indicating that hexagonal boron nitride nanosheets were successfully prepared in Examples 1-10.
[0110] (2) The SEM morphology of the powder samples obtained in step 8 of Examples 1, 3, and 4 was tested. The results are shown in [the table below]. Figure 3 .
[0111] Figure 3 In (f), the product is shown to be a mixture of hexagonal boron nitride nanosheets (indicated by red arrows) and MgO (indicated by orange arrows). The generated h-BN exhibits typical lamellar characteristics, with its lamellars embedded vertically into the MgO crystal matrix. By comparison... Figure 3 (a) to Figure 3 (f) shows that as the proportion of MgO increases, the thickness of the hexagonal boron nitride nanosheets gradually decreases, from 0.2 μm to less than 0.05 μm. These results indicate that the thickness of the hexagonal boron nitride nanosheets in the product can be controlled by adjusting the MgO content in the reactants, thus adjusting its thickness from the micrometer scale to the nanometer scale.
[0112] (3) The XRD characterization spectra of the hexagonal boron nitride nanosheets of Example 1 before and after acid washing were tested. The results are shown in […]. Figure 4 .
[0113] Depend on Figure 4 It can be seen that the product phase after acid washing is only hexagonal boron nitride nanosheets. Two strong peaks were observed at 26° and 41° of the 2θ angle, which correspond to the (002) and (100) planes of the hexagonal boron nitride nanosheets, respectively. This indicates that the acid washing treatment effectively removed the by-products in the combustion synthesis product and obtained high-purity single-phase hexagonal boron nitride nanosheets with ideal crystallinity.
[0114] (4) SEM images of the hexagonal boron nitride nanosheets from Example 4 were obtained. The results are shown in [Figure 4]. Figure 5 .
[0115] Depend on Figure 5 It can be seen that the acid-washed hexagonal boron nitride nanosheets exhibit unique sheet structure characteristics, with a maximum width of tens of micrometers and a minimum thickness of tens of nanometers.
[0116] (5) The high-resolution HRTEM and electron diffraction images of the hexagonal boron nitride nanosheets from Example 4 were tested. The results are shown in […]. Figure 6 .
[0117] Depend on Figure 6 As shown in (a), the synthesized hexagonal boron nitride nanosheets exhibit clear edge and corner features. The high-resolution image within the red box in (a) indicates that the atoms of the hexagonal boron nitride nanosheets are arranged in a hexagonal symmetry, forming a honeycomb lattice feature. The results in (c) show typical single-crystal structure features.
[0118] (6) The AFM of the hexagonal boron nitride nanosheets of Examples 1-10 and Comparative Example 1 was tested. The AFM results of Example 4 are shown in [reference needed]. Figure 7 .
[0119] Depend on Figure 7 It is known that the hexagonal boron nitride nanosheets are composed of single-crystal hexagonal boron nitride, the thickness of which ranges from 10 nm to 20 nm and the length ranges from 5 μm to 8 μm; the aspect ratio of the single-crystal hexagonal boron nitride nanosheets is 250 to 800.
[0120] The thickness and aspect ratio of the single-crystal hexagonal boron nitride nanosheets in other embodiments all fall within the above ranges; while the thickness of the single-crystal hexagonal boron nitride nanosheets in Comparative Example 1 is 2 to 10 μm, and the aspect ratio is 10 to 20.
[0121] (7) Repeat Example 4, except that the total amount of the mixture was successively increased to 2000g / batch, 300g / batch, 500g / batch, and 1000g / batch. The XRD of the hexagonal boron nitride nanosheets obtained in each batch was tested, and the results are shown in […]. Figure 8 As shown.
[0122] Depend on Figure 8 It can be seen that when the combustion synthesis product is increased from 200g / batch to 1000g / batch, the product mainly has two phase structures: h-BN and MgO, and the XRD diffraction patterns of the batch products are basically consistent. This result indicates that the preparation method of the present invention has good batch stability for large-scale synthesis of hexagonal boron nitride nanosheets.
[0123] Application Example 1
[0124] A series of aluminum alloy finned heat sinks were prepared by spraying a heat dissipation coating containing hexagonal boron nitride nanosheets from the above embodiments and comparative examples onto the surface of a series of aluminum alloy fins of the same specifications. The process included the following steps:
[0125] S1. Place 75g of hexagonal boron nitride nanosheets, 1g of silane coupling agent KH550, 20g of organosilicon resin RSN-0840, and 20g of xylene solvent in a planetary gravity disperser and disperse at high speed for 15 minutes at a dispersion speed of 1500 rpm to obtain a uniformly dispersed slurry for use as a heat dissipation coating.
[0126] S2. The prepared heat-dissipating coating is sprayed onto the surface of the aluminum alloy fins and cured at 180°C for 3 hours to obtain an aluminum alloy finned heat sink with a heat-dissipating coating (approximately 45 micrometers thick). The aluminum alloy finned heat sinks containing the hexagonal boron nitride nanosheets from the above embodiments are designated A1-A10, and the aluminum alloy finned heat sinks containing the hexagonal boron nitride nanosheets from the above comparative examples are designated D1 and D2, respectively.
[0127] Application Example 2
[0128] A series of aluminum alloy finned heat sinks were prepared by spraying a heat dissipation coating containing hexagonal boron nitride nanosheets from the above examples and comparative examples onto the surface of a series of aluminum alloy fins with the same specifications as in Application Example 1. The process included the following steps:
[0129] S1, hexagonal boron nitride nanosheets were dispersed in an aqueous solution of sodium hydroxide with a mass percentage of 10%, and reacted at 150°C for 2 hours to obtain hydroxylated hexagonal boron nitride nanosheets.
[0130] S2, 75g of hydroxylated hexagonal boron nitride nanosheets, 1.5g of silane coupling agent KH550, and 20g of xylene solvent were placed in a grinding and dispersing machine and dispersed at high speed for 15 minutes to obtain a uniformly dispersed slurry, which is then used as a heat dissipation coating.
[0131] S3. Immerse the aluminum alloy fins in a 3 mol / L hydrochloric acid solution for 3.5 min to make their surface roughness 1.5-1.8 μm;
[0132] S4. Spray silane coupling agent KH550 onto the surface of the aluminum alloy fins from step S3 to completely wet the surface. Then, spray the heat dissipation coating from step S2 onto the surface and heat-cur it into a film at 180°C for 3 hours to obtain an aluminum alloy finned heat sink including a heat dissipation coating (approximately 45 micrometers thick). The aluminum alloy finned heat sinks containing the hexagonal boron nitride nanosheets from the above embodiments are designated as B1-B10.
[0133] Test Example 2
[0134] The tests included the thermal conductivity and heat transfer efficiency improvement rate of aluminum alloy finned heat sinks with heat dissipation coatings. The heat transfer efficiency testing equipment included... Figure 9As shown, different heat loads were applied to the aluminum alloy finned heat sink to maintain its temperature between 80-100℃. When the temperature of the aluminum alloy finned heat sink was fixed, the input power of the ceramic heating element to maintain this temperature was P0. After the aluminum alloy finned heat sink was coated, the input power of the ceramic heating element was P1 at the same heating temperature. The heat transfer efficiency of the coating (η) = ((P1-P0) / P0)*100%. Some test results are shown in Table 2.
[0135] Table 2:
[0136]
[0137]
[0138] As shown in Table 2, compared with Comparative Examples 1-2, the hexagonal boron nitride nanosheets of Examples 1-10 have higher thermal conductivity and heat transfer efficiency when used in aluminum alloy finned heat sinks; and the spraying method of Application Example 2 can further improve the thermal conductivity and heat transfer efficiency of the heat sink compared with Application Example 1.
[0139] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing hexagonal boron nitride nanosheets, characterized in that, Includes the following steps: A mixture of magnesium powder, magnesium oxide powder, and boron oxide powder is placed in a reaction vessel, vacuumed, and then nitrogen is introduced to carry out a magnesium thermal combustion synthesis reaction. The resulting solid product is cooled to room temperature and then acid-washed to obtain the hexagonal boron nitride nanosheets. The pressure of the nitrogen gas introduced is 0.1-1 MPa. The magnesium oxide powder has a D50 of 200-300 nm and a D90 of 400-500 nm; the magnesium oxide powder accounts for a molar ratio of more than 0.3 in the mixture; and the molar ratio of boron oxide powder to magnesium powder is 1-2:2-4. The hexagonal boron nitride nanosheets prepared by the method are composed of single-crystal hexagonal boron nitride nanosheets with a thickness of 10-20 nm, a length of 5-8 μm, and an aspect ratio of 250-800.
2. A hexagonal boron nitride nanosheet prepared by the preparation method of claim 1.
3. A heat-dissipating coating, characterized in that, Including the hexagonal boron nitride nanosheets as described in claim 2.
4. An aluminum alloy heat sink, characterized in that, It includes an aluminum alloy substrate and a heat dissipation coating disposed on the aluminum alloy substrate, wherein the heat dissipation coating includes the hexagonal boron nitride nanosheets as described in claim 2, or is made from the heat dissipation coating as described in claim 3.
5. The aluminum alloy radiator according to claim 4, characterized in that, Prepared by a method including the following processes: 1) The hexagonal boron nitride nanosheets, silane coupling agent, organosilicon resin and solvent are mixed to obtain a heat dissipation coating; 2) Apply the heat dissipation coating to the surface of the aluminum alloy substrate and perform a curing process.
6. The aluminum alloy heat sink according to claim 4, characterized in that, Prepared by a method including the following processes: 1) The hexagonal boron nitride nanosheets were dispersed in an alkaline solution and then heated to obtain hydroxylated hexagonal boron nitride nanosheets; 2) The hydroxylated hexagonal boron nitride nanosheets, silane coupling agent, and solvent are mixed to obtain a heat dissipation coating; 3) Immerse at least one surface of an aluminum alloy substrate in an acid solution for a period of time to obtain an aluminum alloy substrate including at least one rough surface, wherein the roughness of the rough surface is 1.5-1.8µm; 4) Spray a silane coupling agent onto the rough surface of the aluminum alloy substrate to form a silane coupling agent bonding layer, and then spray the heat dissipation coating and perform a curing treatment.
7. The aluminum alloy radiator according to claim 5 or 6, characterized in that, The following equations 1-2 must be satisfied: 0.1≤(MN) / N≤0.15 Equation 1, 30µm≤Q≤50µm Equation 2, Where M is the heat exchange efficiency of the aluminum alloy radiator under conditions of 80~100℃, N is the heat exchange efficiency of the aluminum alloy substrate under conditions of 80~100℃, and Q is the thickness of the heat dissipation coating.
Citation Information
Patent Citations
Preparation method of organic silicon modified boron nitride heat dissipation coating
CN114507465A
Preparation of boron nitride powder byself-propagation high temparature synthesis
KR1020010049338A
